2001
DOI: 10.1046/j.1365-2648.2001.01900.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of body image, happiness and satisfaction in adolescents wearing a Boston brace for scoliosis treatment

Abstract: Adolescents with scoliosis face problems during bracing and they need to be supported by health care professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
1
10

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 28 publications
7
70
1
10
Order By: Relevance
“…Gender differences in compliance were also found in another study [36]. The authors looked at perceptions of body image, happiness and satisfaction in male and female adolescents wearing the Boston brace.…”
Section: Discussionmentioning
confidence: 75%
“…Gender differences in compliance were also found in another study [36]. The authors looked at perceptions of body image, happiness and satisfaction in male and female adolescents wearing the Boston brace.…”
Section: Discussionmentioning
confidence: 75%
“…Thanks to cultural and language adaptation, we obtained tools that are methodologically correct in assessing the condition of patients who are subject to conservative therapy. Many times when considering mental implications of scoliosis, it has been observed that physical problems and aesthetic issues related to the disease and treatment itself affect the way patients perceive themselves and the type of stress they experience [2,10,12,14,15,19,22]. Danielsson et al on the other hand studied patients who were treated with braces in a 20 year long observation.…”
Section: Discussionmentioning
confidence: 99%
“…Due to stress they have the right to feel the negative emotions like anger among others. In some patients' case, anger may be externalized more in a direct manner, for example by shouting, raising voice tone (as it is in the case of external anger), while in others anger may be hidden, repressed, not shown to the object of a situation (internal anger) [6]. A difficult situation, a long-term illness, physical deficiency or hospitalization and surgery can often trigger reactions of anger which can be expressed directly or suppressed.…”
Section: Introductionmentioning
confidence: 99%